2009
DOI: 10.1007/s00330-009-1497-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective dose evaluation of multidetector CT examinations: influence of the ICRP recommendation in 2007

Abstract: We compared effective doses for recent computed tomography (CT) examinations calculated based on International Commission on Radiological Protection publication number 103 (ICRP 103) with those calculated based on ICRP publication number 60 (ICRP 60), and considered the usefulness of the effective dose in CT dose evaluation. After placing radiophotoluminescence glass dosimeters (RPLDs) inside or outside an anthropomorphic phantom, we examined from the chest to the pelvis, cardiac, and cranial regions of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…When using the new ICRP 103 weighting factors the effective doses at CCTA were significantly higher than when using the outdated ICRP 60 weighting factors (29.9 mSv compared to 24.2 mSv, p<0.0001). This is in accordance with previously published data (73,74). The large difference in calculated dose between the two protocols is probably due to the great increase in tissue weighting for breast, from 0.05 to 0.12, when updating the ICRP 60.…”
Section: Commentssupporting
confidence: 92%
“…When using the new ICRP 103 weighting factors the effective doses at CCTA were significantly higher than when using the outdated ICRP 60 weighting factors (29.9 mSv compared to 24.2 mSv, p<0.0001). This is in accordance with previously published data (73,74). The large difference in calculated dose between the two protocols is probably due to the great increase in tissue weighting for breast, from 0.05 to 0.12, when updating the ICRP 60.…”
Section: Commentssupporting
confidence: 92%
“…Achenbach et al (13) also reported that prospective ECG‐triggered high‐pitch spiral (HPS) CTCA provided excellent image quality at a consistent dose below 1.0 mSv in nonobese patients with low and stable heart rates. Although the effective dose is regarded as the best available dose descriptor for quantifying stochastic risks in diagnostic radiology, one previous study demonstrated that effective doses were comparatively lower than doses absorbed by certain pericardial tissues on CTCA, and that it was preferable to indicate measurable organ‐absorbed doses at the same time (14) . In addition, evaluation of the physical image qualities, such as the noise power spectrum (NPS), 15 , 16 modulation transfer function (MTF), 17 , 18 slice sensitivity profile (SSP), 19 , 20 and the number of artifacts, is also important to confirm the effectiveness of HPS, SAS, and LPS modes.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of dose reduction strategies on radiation exposure. 15 the methodology portion of investigations on radiation dose also tend to not describe which portions of the ctca examination are included in their calculations, whether it be limited to the angiography portion or all the entire dose applied to the subject. The horizontal aspect represents time, the longer the CT beam is active, the more radiation exposure.…”
Section: Discussionmentioning
confidence: 99%